Dancing backwards in high heels: Female professors experience more work demands and special favor requests, particularly from academically entitled students - El-Alayli, Amani; Hansen-Brown, Ashley A.; Ceynar, Michelle (Sex Roles, 2018)
Although the number of U.S. female professors has risen steadily in recent years, female professors are still subject to different student expectations and treatment. Students continue to perceive and expect female professors to be more nurturing than male professors are. We examined whether students may consequently request more special favors from female professors. In a survey of professors (n = 88) across the United States, Study 1 found that female (versus male) professors reported getting more requests for standard work demands, special favors, and friendship behaviors, with the latter two mediating the professor gender effect on professors’ self-reported emotional labor. Study 2 utilized an experimental design using a fictitious female or male professor, with college student participants (n = 121) responding to a scenario in which a special favor request might be made of the professor. The results indicated that academically entitled students (i.e., those who feel deserving of success in college regardless of effort/performance) had stronger expectations that a female (versus male) professor would grant their special favor requests. Those expectations consequently increased students’ likelihood of making the requests and of exhibiting negative emotional and behavioral reactions to having those requests denied. This work highlights the extra burdens felt by female professors. We discuss possible moderators of these effects as well as the importance of developing strategies for preventing them. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: amériques; approches et analyses; discipline; femmes professeures; milieux universitaires; projet charge mentale; psychologie; psychologie sociale; rapports sociaux de sexe; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; travail émotionnel; états-unis

Linking job work hours to women’s physical health: The role of perceived unfairness and household work hours - Thomas, Candice L.; Laguda, Emem; Olufemi-Ayoola, Folasade; Netzley, Stephen; Yu, Jia; Spitzmueller, Christiane (Sex Roles, 2018)
Although the relationship between job work hours and women’s physical health has been examined, limited empirical research examines the family demand conditions that explain this relationship. Given the challenge of integrating work and family demands, we examine the boundary conditions under which job hours relate to women’s physical health by integrating the influences of household work hours, perceived unfairness of division of household labor, and traditional gender ideology. Using a large, multi-national archival dataset, our results show that women working long job hours are more likely to report decreased physical health and that this relationship is moderated by the hours and fairness perceptions of household labor: The lowest physical health was observed at high job hours and high household hours and also when women felt that they did less than their fair share of household labor. However, looking at the slopes of these relationships, the negative relationship between job hours and physical health was stronger when women worked lower household hours or felt that they contributed less than their fair share of household labor—suggesting that maintaining a contribution to household labor might be important for working women. Furthermore, these results suggest that policy and organizational interventions aimed at supporting women’s physical health could take their household labor contributions and fairness perceptions into account when assessing the negative impact of high job work hours. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; conciliation famille-travail; culpabilité; discipline; division sexuelle du travail; projet charge mentale; psychologie; psychologie sociale; périodes historiques; rapports sociaux de sexe; sciences humaines; thématiques; travail; travail domestique

Étude-action sur les discriminations multifactorielles envers les femmes dans trois quartiers prioritaires lyonnais - Vinet, Elise; Cadel, Cynthia; Fieulaine, Nicolas; Colombani, Colline; Béal, Arnaud; Deschamps, Gaëlle; Levasseur, Elodie; Lin, Elise Chane Sha; Clement, Morgan; Laurent, Stéphanie; Vermillon, Marie-Amandine (GRePS-UL2, Région Rhône-Alpes, Ville de Lyon, 2013)
Les femmes des quartiers prioritaires lyonnais vivent-elles des formes spécifiques de discrimination, en particulier dans leurs usages de l’espace public (dans et hors-quartier) ainsi que dans leurs rapports aux offres socio-éducatives et de loisir au sein même de ces quartiers ? Ces discriminations tiennent-elles à leur sexe, à leur genre, à leur âge, à leur appartenance à un quartier classé en politique de la ville, à leur confession le cas échéant, à leur racisation par la société le cas échéant, racisation régulièrement qualifiée d’ « origine ethnique » ? A l’enchevêtrement inextricable de ces facteurs ? Le focus sur la catégorie « femme », bien que couplé à d’autres facteurs, ne risque-t-il pas d’invisibiliser d’autres formes de discriminations vécues sur ces territoires qui englobent la question des rapports sociaux de sexe sans s’y réduire pour autant ? Ces formes de discriminations sont-elles liées à des problématiques propres à ces territoires et/ou sont-elles liées à des problématiques systémiques venant s’incarner de diverses façons sur ces territoires ? Les professionnel-le-s territoriaux ainsi que celle-ceux des structures socio-éducatives et de loisir sont-elles en prise avec des formes de discrimination spécifiques ? Le cas échéant, se sentent-elles outillé-e-s pour y faire face ? Enfin, au vu de ces questionnements, quelles orientations sont envisageables pour l’action publique ? Au moment du bilan, c’est à l’ensemble de ces questions que s’attèle le présent rapport, rendant compte d’une étude-action commandée (par appel d’offre) par la Ville de Lyon (à l’intersection de deux délégations –Egalité femmes-hommes, temps de la ville et handicap et Politique de la ville- et accompagnée par la Mission Egalité de la Ville de Lyon) et conduite par l’équipe EgaliTer’ du laboratoire GRePS.
Keywords: approches et analyses; discipline; droits des femmes*; environnement; europe; france; projet charge mentale; psychologie; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Diversité sexuelle et constructions de genre - Chamberland, Line; Frank, Blye W.; Ristock, Janice L. (Collection Santé et societé, 2009)
Les sciences sociales et épidémiologiques contemporaines tendent de plus en plus à prendre en compte la question du genre dans leurs théories sur les orientations sexuelles. Elle mettent ainsi en évidence les diverses articulations entre les formes de sexisme et d'homophobie, et leurs impacts différenciés selon les constructions du genre et les orientations sexuelles, de même qu'en fonction du contexte socioculturel dans lequel elles se situent. Réalisé avec l'appui de l'équipe pancanadienne Sexualités et genres, vulnérabilité et résilience (SVR), cet ouvrage regroupe des contributions de chercheurs francophones et anglophones du Québec, du Canada, de la France et de la Suisse romande, qui examinent les dimensions socioéconomiques, progessionnelles, familiales, relationnelles et psychologiques afin de saisir les variations liées au genre au sein des minorités sexuelles. Faisant appel à des résultats de travaux multidisciplinaires qui s'appuient sur des méthodologies de types quantitatif et qualitatif, ce livre met en lumière des processus contribuant aux inégalités sociales dans les champs de l'éducation, de l'économie et de la santé, et à des condition de vulnérabilité qui affectent l'estime de soi, les réseaux de soutien et la vie sociale. Les recherches observent des modes de résilience significatifs qui, là encore, peuvent varier en fonction du genre, suggérent ainsi sa prise en compte dans les interventions.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; lesbophobie; premier cycle; psy4910; psychologie; rapports sociaux de sexe; ressource en ligne; sciences humaines; sciences sociales; sexe/genre; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; théorie du genre; épistémologie; études de genres

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Fonctionnalisme, darwinisme et psychologie des femmes. Études d'un mythe social - Schields, Stéphanie A. (La différence des sexes : questions de psychologie, 1986)
Keywords: 1900-1999; approches et analyses; cours; différence des sexes; discipline; europe; fem1000; france; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines